Decision Making Process of Workign Resignation in Mothers with Down Syndrome Children - Stella Vania; Penny Handayani (The Center for Disability Studies and Services Brawijaya University, 2018)
The aim of this study is to explore the decision-making process of working resignation passed by mothers with Down syndrome children. Children with Down syndrome need more attention because of their limitations in terms of cognitive, behavior and health. Mother's role is needed to optimize their development. However, being full time mothers is not easy. In the case of families with economic limitations, mothers often have to work. Further more, Down syndrome children need special care and education that require large costs. Therefore, mothers will go through a long process with various considerations when she decided to resign. This research uses qualitative method through narrative approach. This study used semi structured interviews with three mothers of Down syndrome children that decided resign from work and take care of her child. The result of this research show that three mothers have gone through the process of decision making with different dynamics, depends on the child's condition.